Single-center experience in 127 adult patients, mono or dual artificial liver support therapy, in patients with acute liver failure - Ocak, Ilhan (Frontiers in Medicine, 2023)
Background Acute liver failure (ALF) is a serious condition characterized by sudden liver dysfunction, jaundice and hepatic encephalopathy. Its mortality rate of approximately 80% underscores the urgent need for effective treatments. Supportive extracorporeal therapies (SET), which temporarily support liver function and remove toxins, have shown promise in improving outcomes in acute liver failure (ALF). The aim of this study was to compare the outcomes of dual supportive extracorporeal therapy (SET) and mono supportive extracorporeal therapy in patients with acute liver failure. Methods A total of 127 patients with acute liver failure were included in this retrospective, single-center study. Of these, 62 patients received dual supportive extracorporeal therapy and 65 patients received mono supportive extracorporeal therapy. Primary endpoints were survival without the need for liver transplantation and mortality. Secondary endpoints included resolution of encephalopathy and normalization of International Normalized Ratio (INR). Results In the dual supportive extracorporeal therapy group, 59.6% of patients survived without the need for liver transplantation, while 27.4% achieved recovery with liver transplantation. The mortality rate in this group was 12.9%. Significant regression of encephalopathy grade was observed in 87% of patients, and the 1 year mortality rate for liver transplant recipients was 10.7%. In the mono supportive extracorporeal therapy group, 61.5% of patients experienced a successful recovery without the need for liver transplantation, with a mortality rate of 29.2%. Significant improvement in the grade of encephalopathy was observed in 70.7% of patients. Conclusion Both dual supportive extracorporeal therapy (CVVHDF and PE) and mono supportive extracorporeal therapy (PE) were associated with significant improvements in renal and hepatic biochemical parameters, blood ammonia levels, and neurological status in patients with acute liver failure associated with grade III-IV hepatic encephalopathy. In particular, dual support was associated with improved hemodynamic stability, lactic acidosis and acid–base balance. Survival in acute liver failure in our retrospective cohort using a protocolized approach to extracorporeal therapies is higher compared to previously published large ALF studies. This protocolized approach warrants further prospective studies.